Pengaruh Metode Latihan Interval Intensif dan Interval Ekstensif terhadap Peningkatan VO2 Max - Muhammad Suhdy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The objective of the study was to demonstrate the effect of intensive and extensive interval training methods on the improvement of VO2Max. This type of research is a quasi experiment using Randomized Pretest-Posttest Design Group research design. The research method used Intensive Interval Training and extensive Interval Training. The results of this study obtained the correlation of both test groups of 0.491 with significance of 0.150, paired sample test, obtained by the mean differences of 3.530. Thit = 3.187 greater than ttab 2.262, with df = 9, P = 0.011. This proves a significant difference in the second group VO2Max intensive interval training test. Next paired sample test, obtained the mean differences of 6.410. Thit = 5.702 greater than ttab 2.262, with df = 9, P = 0.000. This proves that there is a significant difference in the VO2Max of both groups of tests of extensive training methods and paired sample test, obtained by mean differences of 8,640. Thit = 10.640 greater than ttab 2.262, with df = 9, P = 0.000. This proves a significant difference in both groups of VO2Max intensive and extensive exercise test methods. Where extensive interval training methods are better than intensive training methods Keywords: Intensive, Extensive, Extensive, Vo2max Intenval Exercise Method